Taxonomic revision of Mozambique dung beetle species in the genus Diastellopalpus van Lansberge, 1886 (Coleoptera: Scarabaeidae: Scarabaeinae) - Daniel, Gimo M.; Strümpher, Werner P.; Josso, Jean-François; Davis, Adrian L.v. (Zootaxa, 2024)
Recently, there has been growing attention paid to the Mozambican dung beetle fauna, including the description of several new species. In this paper, we revise the taxonomy of species recorded from Mozambique in the genus Diastellopalpus van Lansberge, 1886, including the description of Diastellopalpus scholtzi Daniel, Strümpher, Josso & Davis, new species. We also report a new country record for Diastellopalpus neavei (d’Orbigny, 1914). Moreover, Diastellopalpus orbignyi Péringuey, 1904 is removed from subjective synonymy with Diastellopalpus infernalis van Lansberge, 1887 and proposed as a valid species. Currently, Mozambique encompasses five valid species of the genus Diastellopalpus, namely: Diastellopalpus infernalis van Lansberge, 1887, D. quinquedens Bates, 1888, D. neavei, D. orbignyi and D. scholtzi, new species. We redescribe the former four species and include an examination of the types of their junior synonyms. Furthermore, we diagnose, illustrate, and provide a distribution map for all five species and compare them to the morphologically most similar species in the genus. We designate lectotypes for the following species-group taxa: Diastellopalpus nyassicus Kolbe, 1901, D. orbignyi, D. quinquedens Bates, 1888, Onthophagus ponderosus Péringuey, 1896, and O. tridepressus d’Orbigny, 1902. Finally, we provide an updated identification key for the species of Diastellopalpus recorded from Mozambique.